Pengaruh Tradisi Jawa "Walik Dadah" terhadap Kesehatan Ibu Postpartum: Literature Review - Rahmawati, Windi Chusniah; Maulida, Adiska Rahma; Fitra, Aura Alviona Fitra Alviona; Mujiyanti, Kharisma Pingky Mujiyanti Pingky; Nuraziiza, Nida’a Astie Nuraziiza Astie; Azellia, Ranum Dyah Titah Azellia Dyah Titah; Dania, Ullaya Nazla (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Postpartum, or the postpartum period, is the period after childbirth that lasts for 6 weeks during which the mother's body recovers and the reproductive organs return to normal. It is important for healthcare professionals, especially midwives, to monitor postpartum mothers carefully as suboptimal implementation can lead to problems and complications such as puerperal sepsis. Walik dadah massage is a practice long recognized in Indonesian culture, especially among postpartum mothers. This study explores the benefits, factors influencing the continuity of the tradition, and its impact on the health of postpartum mothers, with a focus on the Javanese cultural perspective From the literature analysis conducted, the walik dadah tradition is considered beneficial in restoring the position of the uterus, stopping postpartum bleeding, and preventing subsequent pregnancies. However, there are also negative impacts such as unwanted bleeding and uterine contractions that can affect postpartum maternal health. Factors influencing the continuity of this tradition include family support, an environment steeped in tradition, habits, beliefs, and community knowledge Although this tradition has become part of cultural identity, it is important to consider its impact on health and make informed decisions based on available medical knowledge. In this context, it is important for healthcare professionals to provide information and understanding to the community about the positive and negative impacts of the traditional practices they adhere to, thereby reducing the risk of health problems that may arise during the postpartum period.